Regime-dependent dynamics of nuclear and coal energy in high-income economies: evidence from a Markov switching analysis - Erdoğdu, Mevsim; Baycan, İsmail Onur (Frontiers in Environmental Science, 2025)
IntroductionNuclear energy remains a key low-carbon source in high-income economies, whereas coal continues to account for a substantial share of greenhouse-gas emissions.MethodsThis study examines the regime-dependent behaviour of per capita nuclear and coal energy production from 1965 to 2023 using a Hidden Markov Model (HMM). Structural breaks, volatility shifts, and persistent production regimes are estimated via the Expectation–Maximisation algorithm and smoothed state probabilities.ResultsThe results indicate strong persistence in the medium- and high-production regimes of nuclear energy, while coal exhibits a gradual yet sustained transition from high toward low regimes, consistent with long-term decarbonisation efforts.ConclusionOverall, regime-switching dynamics highlight differing adjustment paths: nuclear production shows cyclical shifts linked to policy/technology cycles, whereas coal reflects a long-run structural decline across high-income economies.